Degradation rate of palm oil mill effluent in bucket fish cultivation - Yusrizal Akmal; Arief Hidayat Zulkifli; Mona Fattya Anisha; Sithra Almunadiya; Irfannur Irfannur; Muliari Muliari (Arwana: Jurnal Ilmiah Program Studi Perairan, 2023)
This study aims to assess the level of degradation of palm oil mill effluent (POME) contamination as a medium for growing kale and catfish in a bucket fish cultivation system. This study used a completely randomized design consisting of four treatments and three replications. The treatments in this study were variations in the concentration of POME added to the culture media consisting of Control (0 mg.L-1), A (1,565 mg.L-1), B (2,347 mg.L-1), and C (3,130 mg.L-1). The test fish used were 5-7 cm catfish, 20 fish per bucket obtained from a local BBI, while the kale used was obtained from commercially sold seeds. Budikdamber maintenance time was conducted for 30 days and then analyzed by ANOVA. The parameters examined included the degradation rate of COD, TSS, phosphate, nitrate, and ammonia, pH, DO, and temperature of the cultivation media. The results showed that there was a decrease in COD, phosphate, nitrate and ammonia levels with increasing LCKS concentration, while TSS degradation showed a decrease with increasing POME concentration. The 3,130 mg.L-1 treatment, although showing a significant decrease in DO levels and an increase in pH, was still within the range allowed in fish cultivation. This indicates that the budikdamber system is less effective in decomposing the POME content and maintaining aquaculture water quality parameters.